THE RELATIONSHIP OF CHEMISTRY TEACHER DELIBERATION (MGMP) ACTIVITIES, AND ACADEMIC SUPERVISION WITH TEACHER PERFORMANCE - Panut; Effendi, Rustam; Saleh, Muhammad (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
The purpose of this research was to determine the relationship between chemistry Teacher Deliberation (MGMP) activities and academic supervision with performance assessment (PKG). It uses a quantitative approach with descriptive methods and correlation techniques. Data were obtained from a sample of 54 chemistry teachers from all Senior High School in Banjarmasin using a questionnaire that tested for validity and reliability. Data were analyzed to determine the relationship between variables using Pearson product-moment and multiple correlations. The results showed there was a positive relationship between MGMP chemistry activities and performance assessment. There was also a positive relationship between academic supervision and performance assessment, as well as between MGMP activities and academic supervision with performance assessment. There is a need for learning to shift from the teacher to the student center as an implication of adopting the 2013 curriculum.